Seafarers’ certification in Ukraine: towards an effective model - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V.; Kivalov, Sergiy (Odesa : Publishing House Helvetica, 2020)
The article is focused on the issues of administrative and corruption obstacles in the sphere of acknowledgement a qualification of seafarers in Ukraine. The ways and means of sterngtheing institutional capacity and optimizing legal regulation of this sphere are defined. The attention is focused on the modern shortcomings of the organization of certification of seafarers in Ukraine, the insufficient national policies and the significant corruption risks. Current Ukrainian legislation and main trends of institutional developments in the field are reviewed. The emphasis is made on the need of implementation of internationally recognized and best foreign practices to improving the efficiency of the seafarers’ certification systems. The EU standards in the sphere of reassessment of third countries are considered, and their application is proposed by Ukraine. Also, the attention is focused on the need to introduce the new IT-technologies into the certification process of seafarers. In addition, the establishment of an audit mechanism of the national certification procedures and, in the conditions of their proper organization, the concession of the right to their domestic implementation are proposed. Summing up, the author outlines a set of ways and means to improve the procedure of certification of seafarers for seafarers in Ukraine. They include: the strict compliance with the requirements of the international agreements and the approximation of national practices to the EU standards; the ensuring transparency in the process of training and certification of seafarers, the introduction of modern IT-technologies for this purpose; the reform of the control’s systems of the educational institutions’ activity, the increasing an interest of seafarers in maintaining integrity when obtaining certificates.

Статтю сфокусовано на питаннях адміністративних та корупційних перешкод у сфері визнання кваліфікації моряків в Україні. Визначено шляхи та засоби укріплення інституційного потенціалу та оптимізації правового регулювання цієї сфери. Увагу акцентовано на сучасних недоліках організації дипломування моряків в Україні, недоліках національної політики та значних корупційних ризиках. Розглядається діюче українське законодавство та основні тенденції інституційного розвитку у цій галузі. Акцент робиться на необхідності впровадження міжнародно визнаних та найкращих зарубіжних практик для підвищення ефективності систем дипломування моряків. Розглядаються стандарти ЄС у сфері переоцінки третіх країн, пропонується їх застосування Україною. Також увагу зосереджено на необхідності впровадження нових ІТ-технологій у процес дипломування моряків. Окрім того, пропонується створення механізму аудиту національних процедур сертифікації та, за умови їх належної організації, надання права на їх застосування. Підводячи підсумок, автор окреслює набір шляхів та засобів вдосконалення процедури дипломування моряків в Україні. Вони включають: суворе дотримання вимог міжнародних угод та наближення національної практики до стандартів ЄС; забезпечення прозорості процесу підготовки та дипломування моряків, впровадження для цього сучасних ІТ-технологій; реформування систем контролю діяльності навчальних закладів, збільшення зацікавленості моряків у збереженні доброчесності при отриманні сертифікатів.
Kivalov S. Seafarers’ certification in Ukraine: towards an effective model / S. Kivalov // Lex Portus. - Odesa : Publishing House Helvetica, 2020. - 5 (25). - Р. 7-33.
Keywords: seafarer; certification; public administration; training of seafarers; maritime activity; моряк; дипломування; публічне адміністрування; підготовка моряків; морська діяльність; Research Subject Categories::LAW/JURISPRUDENCE